Terrestrial and unmanned aerial vehicle images and point clouds of the Rotmoos valley near Obergurgl, Austria with coordinates of corresponding ground control points acquired during the Innsbruck Summer School of Alpine Research [dataset] - Pfeiffer, Jan; Scaioni, Marco; Rutzinger, Martin; Adams, Marc; Graf, Armin; Sotier, Bernadette; Höfle, Bernhard; Lindenbergh, Roderik; Oude Elberink, Sander; Pirotti, Francesco; Bremer, Magnus; Zieher, Thomas; et al. (PANGAEA - Data Publisher for Earth & Environmental Science, 2019)
Structure-from-Motion (SfM) and dense matching are consolidated techniques for automated point cloud generation from images. A camera installed in the payload of a fixed-wing unmanned aerial vehicle (UAV) allows to reconstruct the terrain topography of a large area like the floor of the Rotmoos valley, while a block of images captured with a ground-based camera may be used for integrating vertical walls, as for example eroded riverbanks. Data-sets can be georeferenced into the same mapping reference frame using coordinates of ground control points (GCPs) measured with a differential global navigation satellite system (DGNSS) or geodetic methods. This data publication contains data acquired during the Innsbruck Summer School of Alpine Research - Close Range Sensing Techniques in Alpine Terrain, which took place in Obergurgl, Austria. With the support of the Austrian Research Centre for Forests (BFW) pictures were captured either from the ground or from an UAV. Additionally, DGNSS and total station devices were used to estimate the coordinates (WGS 84 / UTM zone 32N; EPSG:32632) of GCPs recognizable within the pictures. To facilitate the recognition of each ground control point within the corresponding picture a sketch identifying their position within a RGB-coloured map is attached. Besides of these photogrammetric raw data, further processed photogrammetric point clouds and data from laser scanning campaigns covering the catchment of the Rotmoos valley are published.
Gesehen am 29.07.2024
Keywords: Forschungsdaten; Datenbank